Intervening to Reduce Inequalities in Infections in Europe - Semenza, Jan C. (American Public Health Association, 2008)
The European Centre for Disease Prevention and Control was founded in response to newly emerging infections such as severe acute respiratory syndrome and avian influenza. However, Europe faces other communicable disease challenges that have proven to be remarkably resilient to public health interventions. We present examples of communicable diseases with inequitable distribution among those with poor educational attainment, low income, or other socioeconomic factors in every European country. Because these findings are incompatible with social justice and fairness, we examine strategic interventions targeting upstream causes of communicable disease transmission keeping in mind 10 indispensable public health functions essential to reach marginalized groups. These interventions have to be tailored to the socio-political context and rely on community-based decision-making and intersectorial collaboration.